Inter-Channel Correlation in the Eeg Activity During a Cognitive Problem Solving Task with an Increasing Difficulty Questions Progression. - Cordova-Gonzalez, F; Palominos-Villavicencio, F; Cifuentes-Alfaro, F; Canete-Arratia, L (Elsevier B.V., 2015)
Correlation analysis allows detecting the degree of relatedness between two variables. Even when correlation does not mean necessarily causation, in a time series, it indicates the degree of synchrony of two comparing variables and in many aspects renders similar information compared with cross-coherence analysis of the electroencephalographic signal. In this work we explore rather simple statistical features to mine into deeper underlying aspects of the functional organization of the brain during performing an intelligence test. We studied time length duration taken to solve a series of questions ordered with increasing difficulty and the correlation values reached by tine series data synchronization between the 14 EEG channels placed in the subject s scalp, during the mental task. The intelligence test consisted in an abbreviated (15 questions) version of the Raven Matrices test. Results coming from the correlation analysis showed relevant information about functional organization strategies of the brain solving a cognitive problem, as well as good discrimination for inter-individual differences in the way inter-channel correlation values distribute differently for each subject around central values of R. ©2015 Published by Elsevier B.V.